Improving Community Competence in Environmental Health Management: A Health Education Literacy Review - Lyna M. N. Hutapea; Dwight Mahaputera Marulitua Hutapea (PT. Anagata Sembagi Education, 2024)
Inadequate community competence in managing environmental health remains a pressing issue across many regions, including Indonesia. This challenge underscores the critical need for comprehensive insights into how health education can play a pivotal role in empowering communities. This research delves into an in-depth systematic literature review, aiming to dissect and assess diverse strategies employed in health education programs to boost the efficiency of environmental health management initiatives. Utilizing the Systematic Literature Review (SLR) approach, this study adheres to the framework provided by PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). The process encompasses key phases: defining precise research inquiries, determining rigorous inclusion and exclusion parameters, and executing an extensive literature search through prominent academic databases such as Google Scholar, PubMed, and Scopus. The search leveraged specific keywords, including